Evaluation of cancer biomarkers as target for breast cancer progression - Abdulameer, Ban Imad; ALAbassi, Hazima Mossa (Iraqi Journal of Science, 2025)
This study aimed to elucidate the roles of heparin, adenosine, N-cadherin, and β-catenin in cancer, with the ultimate goal of identifying a novel therapeutic target that can be combined with chemotherapy to enhance the host immune response against cancer. A pilot study was conducted in the main medical hospital in Baghdad (medical city-oncology teaching hospital). A total of 60 blood samples were collected from women with breast cancer aged 25-65 years, along with 30 blood samples from apparently healthy women aged matched with patients. The samples were divided into three groups: 30 newly diagnosed patients untreated breast cancer, 30 patients undergoing chemotherapy (Adriamycin + cyclophoshomide), and 30 health control individuals. Three millilitres peripheral blood samples were drawn from each participant. Serum was isolated, and an ELISA assay was carried out to determine serum level of studied parameters. The results indicated a significant increasing in the serum level of heparin, adenosine, N-cadherin and β-catenin in all patients (early diagnosed and treated) versus control. Additionally, there were significant differences in serum level of patient’s according to the age, stage, grade of disease and patient’s hormonal status of some studied parameters. In conclusion, all studied parameters may consider a good therapeutic target to stop the breast cancer progression.